Genicular artery embolisation versus sham embolisation for symptomatic osteoarthritis of the knee: a randomised controlled trial - Sita M A Bierma-Zeinstra; Edwin H G Oei; Adriaan Moelker; P Koen Bos; Tijmen A van Zadelhoff; Rianne A van der Heijden (BMJ Open)
Objective To determine the efficacy of genicular artery embolisation (GAE) compared with sham GAE for pain reduction in patients with symptomatic mild-to-moderate knee osteoarthritis (KOA).Design Double-blind randomised sham-controlled clinical trial conducted from June 2019 to December 2021. The follow-up period was 4 months.Setting Single-centre study conducted at a university medical centre in Rotterdam, Netherlands.Participants 58 adults with symptomatic mild-to-moderate KOA not improving with conservative treatment.Interventions Participants were randomised to receive either GAE treatment or a sham GAE treatment.Main outcome measures The primary outcome was reduction of pain measured with the Knee Injury and Osteoarthritis Outcome Score pain subscale (0–100, with 0 representing the worst pain outcome and 100 the best) after 4 months. Outcomes were assessed at baseline and 1 and 4 months.Results From June 2019 to December 2021, 58 patients were included. 29 patients were randomised to the GAE group and 29 to the sham group. All participants completed the study. The mean pain reduction after 4 months was 21.4 (95% CI 13.9 to 28.8) for the GAE group and 18.4 points (95% CI 11.6 to 25.1) for the sham group. The between-group difference for the mean pain reduction was 3.0 (95% CI −7.1 to 13.0) with an estimated Cohen’s d effect size of d = 0.15 (95% CI −0.37 to 0.66). Group allocation was not a significant contributor to pain reduction (p = 0.31). No serious adverse events (AEs) occurred. 23 mild AEs occurred in the GAE group and 5 in the sham group.Conclusion We did not establish a clinical effect of GAE in patients with mild-to-moderate KOA as GAE produced a similar effect on pain reduction as a sham GAE procedure.Trial registration number NCT03884049.